STRATEGI IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH DALAM MENINGKATKAN MUTU PEMBELAJARAN DI UPTD SDN 54 DUALIMPOE KECAMATAN MANIANGPAJO KABUPATEN WAJO - Faridah; Muhammad Arafah; Tenri Sau (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the implementation strategy of School-Based Management (SBM/MBS) in improving the quality of learning at UPTD SDN 54 Dualimpoe, Wajo Regency. SBM provides autonomy for schools to manage resources independently and participatively. This research employs a qualitative approach with data collection techniques through interviews, observations, and documentation. The results indicate that the implementation of SBM at UPTD SDN 54 Dualimpoe has been well-executed, covering curriculum management, student affairs, teacher professionalism development, and systematic, transparent financial management. The relationship between the school and the community is harmoniously maintained through socialization and active stakeholder participation. The main supporting factors are teacher discipline, democratic decision-making principles, and the commitment of educators. However, identified barriers include limited understanding of the SBM concept among some educators and central policy interventions that restrict school flexibility. The conclusion affirms that SBM contributes significantly to school program effectiveness and improved learning quality through managerial autonomy.